Criteria of operational technical maintenance efficiency estimation in reorganization of "Syrian Arab Airlines" - Василенко, В. А.; Нуралдин, Мутлак (Proceedings of National Aviation University (archive), 1999)
Considered are theoretical and practical problems in formation of estimation criteria of multi- factor process going on in multidimentional space of operating technical maintenance requirements of reformed system of civil aviation transportation in state "Syrial company "Syrian Arab Airlines"